RANCANGAN WAHANA ALAT PERAGA UNTUK MENGENALKAN KONSEP PRODUKTIVITAS DAN EFISIENSI KEPADA GENERASI MUDA - Subarman, Karya; Setiawan, Achmad Hanafi (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
To make Indonesia an industrial country, it requires appropriate quality of human resources, especially for the younger generation who in turn will become the nation’s successors. Education in the field of science is one means to be able to meet these needs. Informal education that utilizes exhibits is designed to provide a more enjoyable atmosphere for the technology concept education process because the material is adapted to the development of science and technology and can be applied in the real world. The Science and Technology Demonstration Center (Science Center) at TMII gradually has a program to complete the exhibits vehicle which currently has 26 galleries, the development of teaching exhibits based on the concepts of productivity and efficiency has been carried out in this research with qualitative research methods and data The collected field is then analyzed reflectively. Of the 20 selected exhibits, they are arranged in the form of 3 cluster designs (area introductory area cluster, application of science principles cluster, and future industrial cluster) and 1 layout design for teaching aids to introduce the concept of productivity and efficiency to the younger generation.